Investigation of novel dexrazoxane analogue JR-311 shows significant cardioprotective effects through topoisomerase IIbeta but not its iron chelating metabolite. (1st December 2017) - Bures, Jan; Jirkovska, Anna; Sestak, Vit; Jansova, Hana; Karabanovich, Galina; Roh, Jaroslav; Sterba, Martin; Simunek, Tomas; Kovarikova, Petra
Graphical abstract: Highlights: A novel analogue of dexrazoxane, JR-311, with similar pharmacodynamics was identified. Cardioprotection of bis-dioxopiperazines is attributed to TOP2B not Fe chelation. Multidisciplinary approach revealed chemical instability of JR-311. Development of dexrazoxane analogues requires early stability testing. Abstract: Novel dexrazoxane derivative JR-311 was prepared to investigate structure-activity relationships and mechanism(s) of protection against anthracycline cardiotoxicity. Its cardioprotective, antiproliferative, iron (Fe) chelation and inhibitory and/or depletory activities on topoisomerase IIbeta (TOP2B) were examined and compared with dexrazoxane. While in standard assay, JR-311 failed in both cardioprotection and depletion of TOP2B, its repeated administration to cell culture media led to depletion of TOP2B and significant protection of isolated rat neonatal ventricular cardiomyocytes from daunorubicin-induced damage. This effect was explained by a focused analytical investigation that revealed rapid JR-311 decomposition, resulting in negligible intracellular concentrations of the parent compound but high exposure of cells to the decomposition products, including Fe-chelating JR-H2. Although chemical instability is an obstacle for the development of JR-311, this study identified a novel dexrazoxane analogue with preserved pharmacodynamic properties, contributed to the investigation of structure-activity relationships and suggested that the cardioprotection of bis-dioxopiperazines is likely attributed to TOP2B activity of the parent compound rather than Fe chelation of their hydrolytic metabolites/degradation products. Moreover, this study highlights the importance of early stability testing during future development of novel dexrazoxane analogues.